(untitled) (Colombia Medica, 1990)
This paper reviews the historical evolution of viewing the psychological aspect as an etiological factor in ulcerative colitis. The process began approximately 60 years ago with the pioneering work of Cecil D. Murray at the New York Presbyterian Hospital. This is a contribution toward a better understanding of the phenomena that play a part in the genesis of this condition within the conceptual framework of a bio-psycho-social perspective